2013
DOI: 10.1647/2012-008r1
|View full text |Cite
|
Sign up to set email alerts
|

Perforating Foreign Body in the Ventriculus of an Umbrella Cockatoo (Cacatua alba)

Abstract: A 4-year-old male umbrella cockatoo (Cacatua alba) with a history of ingestion of foreign material from chewing on a household appliance presented for lethargy, inappetance, and regurgitation of 2 days duration. Foreign bodies identified on radiograph included a wire 2 cm in length in the proventriculus, a wire 3 cm in length in the ventriculus, and several pieces of rubber and plastic throughout the gastrointestinal tract. Diagnosis of a perforating ventricular foreign body was made through plain and contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 22 publications
1
24
0
2
Order By: Relevance
“…Perforation and diverticula formation of the ventriculus have been reported as pathological findings resulting from accidental ingestion of artificial material in bird species [5][6][7]. In our case, perforation and diverticula formation were not observed and the mucosal lesion could not be detected because postmortem changes in the internal organs were too advanced.…”
mentioning
confidence: 53%
“…Perforation and diverticula formation of the ventriculus have been reported as pathological findings resulting from accidental ingestion of artificial material in bird species [5][6][7]. In our case, perforation and diverticula formation were not observed and the mucosal lesion could not be detected because postmortem changes in the internal organs were too advanced.…”
mentioning
confidence: 53%
“…Similarly, Omar (2014) reported that use of litter for bedding in enclosures of tigers in captivity caused ingestion of straw which was subsequently recovered at post mortem examination. According to several authors (Boag et al, 2005;Hayes, 2009;Hoefer and Levitan, 2013) foreign body ingestion occurs commonly in pets and the problem is on the increase (Cornell and Koenig, 2015). The problem is also now increasingly being reported in wild animals (Eckermann-Ross, 2014;Omar, 2014;Squarre et al, 2015), parrots (Hoefer and Levitan, 2013), aquatic (Mousa et al, 2014) as well as marine animals (De Majo et al, 2016;Williams et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…According to several authors (Boag et al, 2005;Hayes, 2009;Hoefer and Levitan, 2013) foreign body ingestion occurs commonly in pets and the problem is on the increase (Cornell and Koenig, 2015). The problem is also now increasingly being reported in wild animals (Eckermann-Ross, 2014;Omar, 2014;Squarre et al, 2015), parrots (Hoefer and Levitan, 2013), aquatic (Mousa et al, 2014) as well as marine animals (De Majo et al, 2016;Williams et al, 2013). It is normal for ingested foreign bodies to perforate the wall of the gastrointestinal tract and end up causing granulomatous lesions in the abdomen (Hoefer and Levitan, 2013;Papazoglou et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…G astrointestinal foreign bodies (FBs) have been reported in a number of avian species, resulting in obstructions in the crop, 1-5 proventriculus, 1,5-10 ventriculus 1,[11][12][13][14][15][16][17][18][19][20] and intestines. [20][21][22][23] Previous reports have described individual cases of FBs composed of wood, 6,7,9 synthetic and natural fibres, 3,9,21,22 feathers, 2,16 stones, 4,9,15 plastics 8,14,17,20 and metal. 5,[10][11][12][13]17,19 Most reported cases in psittacine birds involve unweaned birds.…”
mentioning
confidence: 99%
“…[20][21][22][23] Previous reports have described individual cases of FBs composed of wood, 6,7,9 synthetic and natural fibres, 3,9,21,22 feathers, 2,16 stones, 4,9,15 plastics 8,14,17,20 and metal. 5,[10][11][12][13]17,19 Most reported cases in psittacine birds involve unweaned birds. 1 Toys, perches and accessories made specifically for pet birds are readily available and include items made from natural and synthetic fibres, which have the potential to be ingested.…”
mentioning
confidence: 99%